Impact of CYP3A4 and CYP3A5 Genetic Variants on Tacrolimus Dosing and Therapeutic Outcomes in Kidney Transplant Recipients (Majalah Kedokteran Bandung, 2026)
Tacrolimus is the cornerstone of immunosuppressive therapy in kidney transplantation; however, its narrow therapeutic index and variable metabolism make dose optimization difficult. Genetic variations in the CYP3A4 and CYP3A5 genes significantly influence tacrolimus metabolism yet limited data are available for Pakistani population. This study aimed to evaluate the association of CYP3A4 and CYP3A5 polymorphisms with tacrolimus dose requirements and post-transplant outcomes in Pakistani kidney transplant recipients.  A case-control study was conducted from January 2022 to December 2022 at Shaikh Zayed Hospital and Pakistan Kidney and Liver Institute. A total of 240 participants, including renal transplant recipients and controls, were enrolled using non-probability purposive sampling. Genotyping of CYP3A4 and CYP3A5 variants was performed using Tetra ARMS-PCR. Clinical data regarding tacrolimus dose requirements and rejection episodes were collected, and statistical analysis was performed using the SPSS version 25. Among the participants, 190 (79.1%) were male and 50 (20.9%) were female. Renal transplant recipients receiving tacrolimus accounted for 57% of the study population, while 43% were controls. Patients with the CYP3A5 expressor genotype required significantly higher tacrolimus doses to achieve target trough concentrations compared to non-expressors (OR=4.060, 95% CI: 2.455–6.715, p
Keywords: CYP3A4; CYP3A5; kidney transplant; pharmacogenetics; Pakistan; tacrolimus